Dark force rising: reawakening and targeting of fetal-like stem cells in colorectal cancer - Fey, Sigrid K.; Vaquero Siguero, Nuria; Jackstadt, René-Filip (Cell reports, 2024)
Stem cells play pivotal roles in maintaining intestinal homeostasis, orchestrating regeneration, and in key steps of colorectal cancer (CRC) initiation and progression. Intriguingly, adult stem cells are reduced during many of these processes. On the contrary, primitive fetal programs, commonly detected in development, emerge during tissue repair, CRC metastasis, and therapy resistance. Recent findings indicate a dynamic continuum between adult and fetal stem cell programs. We discuss critical mechanisms facilitating the plasticity between stem cell states and highlight the heterogeneity observed upon the appearance of fetal-like states. We focus on therapeutic opportunities that arise by targeting fetal-like CRC cells and how those concepts can be translated into the clinic.
Online verfügbar: 23. Mai 2024
Gesehen am 25.11.2024